Estudio de factibilidad para la exportación de arándanos azules deshidratados del departamento de Boyacá con destino al mercado de Florida -Estados Unidos (2023)
The department of Boyacá, in Colombia, offers favorable climatic conditions and suitable land for the production of high-quality blueberries. With the aim of adding value to this Colombian agricultural product, a feasibility study has been conducted to assess the viability of exporting dried blueberries to the market in Florida, United States.